Reformasi Pemikiran dan Praktik Pendidikan Islam: Analisis Komparatif atas Gagasan Muhammad Qasim Zaman di Timur Tengah dan Asia Selatan (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2025)
This article explores the reform of Islamic educational thought and practice through a comparative analysis of Muhammad Qasim Zaman's perspectives on the Middle East and South Asia. The method used in this research is qualitative, using content analysis techniques on Zaman's book, Modern Islamic Thought in a Radical Age: Religious Authority and Internal Criticism, as well as Zaman's other books and writings. The analysis focuses on how religious authority, the role of clerics, and political engagement affect Islamic educational institutions and discourses. The findings show that Zaman presents a critical reflection on the intersection between tradition and modernity in both regions, demonstrating how educational reforms were shaped by debates between traditionalist and modernist currents. These dynamics contributed to the formation of new educational models-such as reformed madrasas and integrated universities-that sought to integrate classical Islamic knowledge with modern sciences. This study highlights Zaman's contribution to understanding the trajectory of Islamic education reform in different socio-political contexts.